Arab Nationalism - Tibi, B. author. aut Link
XVII, 365 p.
Keywords: The third edition includes a new Part Five on the tensions between Arab nationalism and Islam arising from the crisis of the nation-state and of the de-legitimisation of Pan-Arab regimes. The effects of the Arab defeat in the Six-Day War 1967 and the rise of political Islam in the 1970s are the focus of the new part. The background of the analysis of the impact and function of nationalism and its contribution to social and political change in the Third World, taking the rise of nationalism in the Middle East as a historical example. Professor Tibi concentrates on the period after the First World War, when many Arab intellectuals became disillusioned with Britain and France as a result of the occupation of their countries. One focus of this study are the writings and influence of Sati' al-Husri on Middle Eastern politics. Professor Tibi illustrates the connection between modern Arab nationalism and nineteenth-century German Romantic nationalism, which will be of particular interest to the English reader. Professor Tibi concludes that while nationalism has played a necessary and important role in the movement for national independence in the Middle East, it has since developed into an ideology which seems to obstruct further social and political emancipation. This third edition, brought completely up to date by a substantial new introduction and two new concluding chapters, will be of particular interest to historians and social scientists dealing with nationalism and crises of the nation-state as well as to students of the Middle East and contemporary Islam.